Triterpenoids from the leaves of Ilex chinensis. (April 2018) - Xia, Wen-Qi; Li, Ruo-Fei; Liu, Jia-Bao; Cui, Bao-Song; Hou, Qi; Sun, Hua; Li, Shuai
Abstract: Eleven previously undescribed compounds including two triterpenes, ilexchinenin A and ilexchinenin B, and nine triterpenoid saponins, ilexchinenosides A-I, along with twelve known triterpenoids were isolated from the leaves of Ilex chinensis Sims (Aquifoliaceae). Their structures were elucidated by spectroscopic analysis and comparison with known compounds. Furthermore, eight compounds exhibited significant inhibitory effects on NO production of lipopolysaccharide (LPS)-induced murine macrophages, while nine compounds exhibited potent hepatoprotective activity against N-acetyl-p-aminophenol (APAP)-induced HepG2 cell damage in in vitro assays. Graphical abstract: Highlights: Eleven unknown triterpenoids were isolated from the leaves of Ilex chinensis. Eight compounds exhibited significant inhibitory activity on NO production. Nine compounds exhibit potent hepatoprotective activity.